Implementasi Kurikulum Merdeka Pada Mata Pelajaran Sejarah di SMA Ar-Rohmah Putri Dau Kabupaten Malang - Nasri, Justica Nur Fitria; Sapto, Ari; Gede Agung, Dewa Agung (Jurnal Pendidikan Sejarah Indonesia, 2025)
The aim of this research is to examine the implementation of the "Kurikulum Merdeka" (Independent Curriculum) in the history subject at SMA Ar-Rohmah Putri Dau in Malang Regency. Purposive sampling is the qualitative research methodology used to select informants who have relevant knowledge and experience. Interviews and observations are utilized to gather data, which is then evaluated using source and method triangulation. The research findings indicate that SMA Ar-Rohmah Putri has been teaching history using the Kurikulum Merdeka since the 2022/2023 academic year. The implementation is being carried out gradually, starting from grade X and will be applied to grade XI in the following academic year. The school has chosen the option of autonomous implementation, with four driving teachers assigned to facilitate a community of learning among the teachers at the school. These findings can provide input for the school and the government in enhancing the implementation of the Kurikulum Merdeka at a broader educational level. Furthermore, this research also provides further insights into the challenges and impacts of adopting an autonomous curriculum in the topic of History at SMA Ar-Rohmah Putri.